LOCAL FILM FESTIVAL CHARACTERISTICS: A CASE STUDY OF THE MERDEKA FILM FESTIVAL - Wangsa, Edelin; Depita, Natalia (Capture : Jurnal Seni Media Rekam, 2023)
Local cinema festival is an alternative form of entertainment for locals. Merdeka Film Festival in Solo, Central Java, is an annual event involving the youth community and local government institutions. This film festival offers entertainment in the form of film screenings on plugged screen (layar tancap). This research mainly seeks to investigate the production pattern of a local film festival. This research employs a descriptive qualitative approach that includes interviews with festival’s organizers and film festival experts. The results indicate that Merdeka Film Festival exhibits the characteristics of local film festival. Besides, the organizers must have a close relationship with the locals through the youth community and local government institutions in order for the film festival to operate smoothly.